Direct regeneration method of failed positive electrode and regenerated positive electrode
By introducing lithium benzoate into the lithium hydroxide/lithium nitrate molten salt system and changing the Li+ transport mechanism, the problem of limited Li+ transport rate in the traditional molten salt method is solved, and efficient repair of failed positive electrodes and good electrochemical performance of regenerating positive electrodes is achieved.
Patent Information
- Application Number
- CN202510022739.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
In the traditional molten salt method, the Li+ transportation rate is limited, resulting in low lithiation efficiency of the surface of the failed positive electrode, affecting the efficient repair effect.
Lithium benzoate is introduced into the lithium hydroxide/lithium nitrate molten salt system, and the rapid "transition" of Li+ is achieved through benzoate, the Li+ transmission mechanism is changed, and the rapid transmission and full lithiation of Li+ are promoted.
Fully lithiation of the failed positive electrode surface is achieved, which ensures efficient structural reconstruction and repair in the subsequent high-temperature calcination stage, and improves the electrochemical performance of the regenerated positive electrode.
Smart Images

Figure CN119833805A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a positive electrode regeneration method, and specifically to a direct regeneration method of a failed positive electrode and a regenerated positive electrode. Background Art
[0002] In recent years, the direct regeneration method of failed LIBs (Lithium-Ion Batteries) has been considered as an economical, environmentally friendly and extremely promising recycling technology due to its simple process flow, low energy consumption, no damage to the positive electrode structure, and the ability to use the recycled positive electrode to re-manufacture new lithium-ion batteries.
[0003] Among many direct regeneration methods, the molten salt method uses the advantage of low eutectic point to lower the reaction temperature, allowing the reaction to proceed between solid and liquid. The ion transfer rate is faster than that of solid-solid reaction, and it can achieve a better repair effect on the failed positive electrode at a lower temperature under normal pressure. Therefore, it has received great attention in recent years. The traditional molten salt method uses thermal drive to make Li + Rapidly transported to the surface of the positive electrode particles to complete the lithiation of the failed positive electrode. + The transport rate reduces the lithiation efficiency on the surface of the failed positive electrode, thereby affecting the efficient repair effect of the failed positive electrode. Summary of the invention
[0004] This application aims at the traditional molten salt method for Li + The limited transport rate leads to the technical problem of low lithiation efficiency on the surface of the failed positive electrode, and a direct regeneration method for the failed positive electrode and a regenerated positive electrode are provided.
[0005] In order to achieve the above objectives, this application adopts the following technical solutions: In a first aspect, the present application proposes a direct regeneration method for a failed positive electrode, comprising: Mixing positive electrode black powder, lithium hydroxide, lithium nitrate and lithium benzoate to obtain a first mixture; Performing a pre-lithiation treatment on the first mixture assembly to obtain a pre-lithiation positive electrode powder; mixing pre-lithiated positive electrode powder and lithium carbonate to obtain a second mixture; The second mixture is sintered to obtain a regenerated positive electrode.
[0006] Furthermore, the addition ratio of positive electrode black powder, lithium hydroxide, lithium nitrate and lithium benzoate is set to 1: (0.2~0.25): (0.25~0.3): 0.5.
[0007] Furthermore, after obtaining the first mixture, the method further comprises: grinding the first mixture under an infrared environment.
[0008] Furthermore, the conditions for the pre-lithiation treatment by assembly include: keeping warm at 300° C. for 4 to 6 hours.
[0009] Furthermore, after the first mixture is pre-lithiated, the method further comprises: Wash with deionized water and centrifuge for multiple times, then dry to obtain pre-lithiated positive electrode powder; Grind the pre-lithiated cathode powder.
[0010] Furthermore, when the pre-lithiated positive electrode powder and lithium carbonate are mixed, the pre-lithiated positive electrode powder and lithium carbonate are added in a molar ratio of 1:(0.25-0.5).
[0011] Furthermore, the conditions for sintering the second mixture include: sintering at 750-850° C. for 6 hours.
[0012] Furthermore, when sintering at 750-850° C., the heating rate is 5-10° C. / min.
[0013] Furthermore, the positive electrode black powder is LiNi 0.5 Co 0.2 Mn 0.3 O2 black fan.
[0014] In a second aspect, the present application proposes a regenerated positive electrode prepared by the direct regeneration method of the above-mentioned failed positive electrode.
[0015] Compared with the prior art, this application has the following beneficial effects: This application proposes a direct regeneration method for failed positive electrodes. Compared with the traditional direct regeneration method of lithium hydroxide and lithium nitrate molten salt, lithium benzoate containing benzoate is introduced into the lithium hydroxide / lithium nitrate molten salt system to repair the positive electrode. The addition of lithium benzoate fundamentally changes the original Li + Transmission mechanism to achieve Li + Stable coupling and decoupling in molten salts to complete Li + This transition promotes the rapid "transition" of Li + The rapid transmission of the positive electrode ensures the full lithiation of the failed positive electrode surface, thereby ensuring the efficient reconstruction and repair of the failed positive electrode structure in the subsequent high-temperature calcination stage. Therefore, the regenerated positive electrode obtained by the direct regeneration method of the present application has good electrochemical performance, providing a promising way for the efficient and sustainable regeneration of spent lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 (a) is a second charge-discharge curve of failed NCM523, regenerated electrode with lithium benzoate added, and regenerated electrode without lithium benzoate added at a rate of 0.5 C; Figure 1 (b) is a long cycle curve of failed NCM523, regenerated electrode with lithium benzoate added, and regenerated electrode without lithium benzoate added at 0.5 C rate; Figure 1 (c) is a charge and discharge capacity decay diagram of the regenerated electrode without adding lithium benzoate; Figure 1 (d) is a charge and discharge capacity decay diagram of the regenerated electrode with lithium benzoate added; Figure 2 (a) is a scanning electron microscope schematic diagram of the RENCM assembled half-cell; Figure 2 (b) is a scanning electron microscope schematic of a REBNCM assembled half-cell.
[0018] Figure 3 This is a schematic diagram of the principle of the direct regeneration method of the failed positive electrode of the present application. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0020] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0021] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0022] In the description of the embodiments of the present application, it should be noted that if the terms "upper", "lower", "horizontal", "inner", etc. appear, the orientation or position relationship indicated is based on the orientation or position relationship shown in the drawings, or the orientation or position relationship in which the invented product is usually placed when used. It is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0023] In addition, if the term "horizontal" appears, it does not mean that the component must be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", which does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0024] In the description of the embodiments of the present application, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0025] Under the trend of global energy structure transformation and pursuit of green and sustainable development, lithium-ion batteries (LIBs), as an important component of energy storage, have seen a sharp increase in demand in various electronic devices, electric vehicles, energy storage systems and other fields. Generally, the life of lithium-ion batteries is only 5-8 years, and it is predicted that 11 million tons of waste lithium batteries will be generated in 2030. More than 30% of the production cost of LIBs is concentrated in the positive electrode, so the current recycling technology is mainly aimed at layered positive electrodes that have been commercially applied, such as lithium cobalt oxide (LiCoO2) and ternary positive electrodes (NCM). At present, the traditional methods for recycling failed layered positive electrodes are mainly pyrometallurgical and hydrometallurgical, but relying on traditional methods to recycle failed LIBs leads to excessive environmental costs and limited economic benefits. In recent years, the direct recycling method of failed LIBs has been considered to be an economical, environmentally friendly and promising recycling technology due to its simple process flow, low energy consumption, no damage to the positive electrode structure, and the ability to use the recycled positive electrode to re-manufacture new lithium-ion batteries.
[0026] Among many direct regeneration methods, the molten salt method uses the advantage of low eutectic point to reduce the reaction temperature. The reaction can be carried out between solid and liquid. The ion transfer rate is faster than that of solid-solid reaction. It can achieve a better repair effect on the failed positive electrode at a lower temperature under normal pressure. Therefore, it has received great attention in recent years. Generally speaking, the molten salt method for repairing failed positive electrodes mainly includes two stages (surface lithiation and subsequent high-temperature calcination). The first stage is to select a suitable molten salt system and heat it at a certain temperature to form a molten state with a low eutectic point to achieve lithiation on the surface of the failed positive electrode, that is, Li + The formation of a lithium-containing complex with the surface of the failed positive electrode provides sufficient lithium source for the defective structural repair of the failed positive electrode in the second stage. The second stage is to reconstruct the surface structure of the failed positive electrode by calcining at high temperature to restore it to a perfect layered structure. In the process of repairing the failed positive electrode with molten salt, the surface lithiation of the failed positive electrode is crucial for the subsequent structural recovery.
[0027] The current conventional molten salt is a thermally driven method to generate Li + Rapidly transported to the surface of the cathode particles to complete the lithiation of the failed cathode. However, due to its limited Li + The transport rate reduces the lithiation efficiency of the failed positive electrode surface, thus affecting the efficient repair of the failed positive electrode. Only by improving the lithiation effect on the surface of the failed positive electrode can the efficient repair of the failed positive electrode be achieved. + The transport efficiency is an important factor affecting the lithiation of the failed cathode surface. + Transport efficiency is the key issue in achieving efficient repair of failed positive electrodes.
[0028] The Grotthuss mechanism was first proposed by Theodore von Grotthuss in 1804. The transport efficiency of hydrogen ions in liquids by hydrogen bonds is much higher than the diffusion efficiency of hydrogen ions relying solely on concentration gradients. The proposal of this mechanism provides a method for improving the transport efficiency of cations. The purpose of this application is to introduce lithium benzoate containing benzoate into the lithium hydroxide / lithium nitrate molten salt system, and use benzoate to achieve Li + Stable coupling and decoupling in molten salts to complete Li + The rapid "jump" of the failed positive electrode realizes the full lithiation of the surface of the failed positive electrode, providing a guarantee for the structural reconstruction and efficient repair of the failed positive electrode in the subsequent high-temperature calcination stage, thereby realizing the efficient repair of the failed positive electrode.
[0029] Based on the above situation, the present application proposes a direct regeneration method of a failed positive electrode and a regenerated positive electrode. The present application is described in detail below in conjunction with embodiments and drawings.
[0030] The present application proposes a direct regeneration method for a failed positive electrode, which may include: Mixing positive electrode black powder, lithium hydroxide, lithium nitrate and lithium benzoate to obtain a first mixture; Performing a pre-lithiation treatment on the first mixture assembly to obtain a pre-lithiation positive electrode powder; mixing pre-lithiated positive electrode powder and lithium carbonate to obtain a second mixture; The second mixture is sintered to obtain a regenerated positive electrode.
[0031] In some embodiments of the present application, the molar ratio of positive electrode black powder, lithium hydroxide, lithium nitrate and lithium benzoate is set to 1: (0.2~0.25): (0.3~0.25): 0.5, and the molar ratio of the former two and the molar ratio of lithium benzoate can be controlled to be 1:1. The molar ratio range of lithium hydroxide and lithium nitrate takes into account the molten salt phase diagram of the two. When the ratio range is 0.4~0.5, both can become molten at a melting temperature of 300 degrees Celsius.
[0032] In some embodiments of the present application, the conditions for pre-lithiation treatment through assembly include: keeping warm at 300°C for 4-6 hours. Too low a holding time makes the pre-lithiation insufficient, and the lithium ions cannot completely complete the lithiation of the failed positive electrode, resulting in poor electrochemical performance. When the lithiation time is extended to more than 6 hours, the electrochemical performance is not completely improved. On the contrary, long-term treatment may cause slight degradation of the material structure.
[0033] In some embodiments of the present application, when the second ground material and lithium carbonate are mixed, the addition ratio of the second ground material and lithium carbonate is 1:0.25~0.5 according to the molar ratio. When the addition range is 0.25~0.5, the lithium loss in the high-temperature calcination stage can be compensated. The electrochemical performance is almost the same. The currently reported amount of lithium carbonate added is 0.5. The experiment of the present application proves that the lower molar ratio of 0.25 does not cause a significant difference in electrochemical performance.
[0034] In some embodiments of the present application, the conditions for sintering the second mixture include: sintering at 750-850°C for 6 hours. Keeping the temperature at 750-850°C for 6 hours, at a lower temperature (below 750°C), the transformation of the rock salt phase to the layered phase is incomplete, resulting in insufficient crystallization, and when the temperature is higher than 850°C, the excessively high temperature will destroy the structure of the material and lead to poor electrochemical performance.
[0035] In some embodiments of the present application, when sintered at 750-850 °C, the heating rate is 5-10 °C / min. Rapid heating may cause uneven temperature inside and on the surface of the material, resulting in thermal stress concentration, thereby inducing cracks or other structural defects, and rapid heating is not conducive to the transformation of the rock salt phase to the layered phase in the failed positive electrode. When the heating rate is lower than 5 °C / min, slow heating may lead to uneven energy distribution, and too slow a heating rate will increase the production cycle, reduce production efficiency, and increase costs.
[0036] It should be noted that, in order to make the mixing more uniform, after obtaining the first mixture and after obtaining the pre-lithiated positive electrode powder, the uniformity of the mixing can be improved by grinding. In addition, when the first mixture is assembled for pre-lithiation treatment, the first mixture can be dispersed in an alumina porcelain boat, and the alumina porcelain boat is used as a carrier, or other carriers can be used according to actual conditions.
[0037] Example 1 (1) LiNi 0.5 Co 0.2 Mn 0.3 O2 is used as positive electrode black powder (denoted as SNCM523). In this embodiment, the positive electrode black powder SNCM523 comes from waste lithium-ion batteries of 3C digital products or electric vehicles, and is processed into positive electrode black powder by a battery recycling company. The positive electrode black powder SNCM523 is a commercially recycled ternary NCM523 positive electrode black powder, and its lithium molar content is between 0.6 and 1.
[0038] (2) SNCM523, lithium hydroxide (LiOH), lithium nitrate (LiNO3) and lithium benzoate (LiC7H5O2) were mixed in a molar ratio of 1:0.2:0.3:0.5 and ground in a mortar for 10 min. Due to the strong water absorption of lithium nitrate (LiNO3), the grinding process can be carried out under an infrared lamp to obtain a first grind.
[0039] (3) The first grind material was evenly dispersed in an alumina porcelain boat and assembled for pre-lithiation treatment at 300 °C for 4 h.
[0040] (4) Wash the powder treated in the previous step with deionized water and centrifuge for 6 times, 3 minutes each time, at a speed of 6000 rpm. In practical applications, the number of washing centrifugation and centrifugation parameters can be adjusted according to actual conditions. Dry the centrifuged powder in an oven at 60 °C for 12 hours to obtain a pre-lithiated positive electrode powder, named SEBNCM.
[0041] (5) After SEBNCM was fully ground in a mortar, SEBNCM was mixed with lithium carbonate (Li2CO3) at a molar ratio of 1:0.25 and ground for 10 min. It was then sintered in a muffle furnace at 850 °C for 6 h with a heating rate of 5 °C / min to obtain a regenerated positive electrode, which was recorded as REBNCM.
[0042] Example 2 (1) LiNi 0.5 Co 0.2 Mn 0.3 O2 is used as positive electrode black powder (denoted as SNCM523). In this embodiment, the positive electrode black powder SNCM523 comes from waste lithium-ion batteries of 3C digital products or electric vehicles, and is processed into positive electrode black powder by a battery recycling company.
[0043] (2) SNCM523, lithium hydroxide (LiOH), lithium nitrate (LiNO3) and lithium benzoate (LiC7H5O2) were mixed in a molar ratio of 1:0.3:0.2:0.5 and ground in a mortar for 10 min. Due to the strong water absorption of lithium nitrate (LiNO3), the grinding process can be carried out under an infrared lamp to obtain a first grind.
[0044] (3) The first ground material was evenly dispersed in an alumina porcelain boat and assembled at 300° C. for a pre-lithiation treatment for 6 h.
[0045] (4) Wash the powder treated in the previous step with deionized water and centrifuge for 6 times, 3 minutes each time, at a speed of 6000 rpm. In practical applications, the number of washing centrifugation and centrifugation parameters can be adjusted according to actual conditions. Dry the powder after centrifugation in an oven at 60°C for 12 hours to obtain a pre-lithiated positive electrode powder, named SEBNCM.
[0046] (5) After SEBNCM was fully ground in a mortar, SEBNCM was mixed with lithium carbonate (Li2CO3) in a molar ratio of 1:0.5 and ground for 10 min. It was then sintered in a muffle furnace at 750 °C for 6 h with a heating rate of 10 °C / min to obtain a regenerated positive electrode, which was recorded as REBNCM.
[0047] Example 3 (1) LiNi 0.5 Co 0.2 Mn 0.3 O2 is used as positive electrode black powder (denoted as SNCM523). In this embodiment, the positive electrode black powder SNCM523 comes from waste lithium-ion batteries of 3C digital products or electric vehicles, and is processed into positive electrode black powder by a battery recycling company.
[0048] (2) SNCM523, lithium hydroxide (LiOH), lithium nitrate (LiNO3) and lithium benzoate (LiC7H5O2) were mixed in a molar ratio of 1:0.25:0.25:0.5 and ground in a mortar for 10 min. Due to the strong water absorption of lithium nitrate (LiNO3), the grinding process can be carried out under an infrared lamp to obtain a first grind.
[0049] (3) The first ground material was evenly dispersed in an alumina porcelain boat and assembled at 300° C. for a pre-lithiation treatment for 5 h.
[0050] (4) Wash the powder treated in the previous step with deionized water and centrifuge for 6 times, 3 minutes each time, at a speed of 6000 rpm. In practical applications, the number of washing centrifugation and centrifugation parameters can be adjusted according to actual conditions. Dry the powder after centrifugation in an oven at 60°C for 12 hours to obtain a pre-lithiated positive electrode powder, named SEBNCM.
[0051] (5) After SEBNCM was fully ground in a mortar, SEBNCM was mixed with lithium carbonate (Li2CO3) in a molar ratio of 1:0.3 and ground for 10 min. It was then sintered in a muffle furnace at 800 °C for 6 h with a heating rate of 8 °C / min to obtain a regenerated positive electrode, which was recorded as REBNCM.
[0052] Example 4 (1) LiNi 0.5 Co 0.2 Mn 0.3 O2 is used as positive electrode black powder (denoted as SNCM523). In this embodiment, the positive electrode black powder SNCM523 comes from waste lithium-ion batteries of 3C digital products or electric vehicles, and is processed into positive electrode black powder by a battery recycling company.
[0053] (2) SNCM523, lithium hydroxide (LiOH), lithium nitrate (LiNO3) and lithium benzoate (LiC7H5O2) were mixed in a molar ratio of 1:0.22:0.28:0.5 and ground in a mortar for 10 min. Due to the strong water absorption of lithium nitrate (LiNO3), the grinding process can be carried out under an infrared lamp to obtain a first grind.
[0054] (3) The first grind material was evenly dispersed in an alumina porcelain boat and assembled for pre-lithiation treatment at 300 °C for 4 h.
[0055] (4) Wash the powder treated in the previous step with deionized water and centrifuge for 6 times, 3 minutes each time, at a speed of 6000 rpm. In practical applications, the number of washing centrifugation and centrifugation parameters can be adjusted according to actual conditions. Dry the centrifuged powder in an oven at 60 °C for 12 hours to obtain a pre-lithiated positive electrode powder, named SEBNCM.
[0056] (5) After SEBNCM was fully ground in a mortar, SEBNCM was mixed with lithium carbonate (Li2CO3) in a molar ratio of 1:0.4 and ground for 10 min. It was then sintered in a muffle furnace at 820 °C for 6 h with a heating rate of 6 °C / min to obtain a regenerated positive electrode, which was recorded as REBNCM.
[0057] Comparative Example: SNCM523, lithium hydroxide (LiOH), and lithium nitrate (LiNO3) were mixed in a molar ratio of 1:0.4:0.6 and ground in a mortar for 10 min. Due to the strong water absorption of lithium nitrate, the grinding process can be carried out under infrared light. The ground sample was evenly dispersed in an alumina porcelain boat and assembled at 300 °C for pre-lithiation treatment for 4 h. The powder treated in the previous step was washed with deionized water and centrifuged 6 times, each time for 3 min, at a speed of 6000 rpm. The centrifuged powder was then dried in an oven at 60 °C for 12 h to obtain a pre-lithiated positive electrode powder named SENCM. After SENCM was fully ground in an agate mortar, SEBNCM was mixed with lithium carbonate (Li2CO3) in a molar ratio of 1:0.25, and after mixing and grinding in a mortar for 10 min, it was sintered at 850 °C in a muffle furnace for 6 h, with a heating rate of 5 °C / min. The resulting regenerated cathode is abbreviated as RENCM.
[0058] In order to verify the effect of the present application, the REBNCM obtained in Example 1 and the RENCM obtained in the comparative example were assembled and buckled for electrochemical performance testing: first, RENCM or REBNCM, carbon black and polyvinylidene fluoride were dissolved in N-methylpyrrolidone at a weight ratio of 8:1:1 to obtain a slurry; then, the slurry was coated on an aluminum foil, dried at 80°C for 6 hours, and then transferred to a vacuum drying oven, and vacuum dried at 120°C for 12 hours to obtain a dried electrode; then, the dried electrode was punched into a 12 mm diameter circle as the positive electrode, and the active material loading was 3-5 mg cm -2 , using a commercial PP2500 separator, the separator size is round with a diameter of 19 mm, the battery case is CR2032, and the button battery is assembled in an argon-filled glove box. The half-cell is assembled using the Li negative electrode.
[0059] Electrochemical performance test and scanning electron microscope test were carried out: a long cycle test was carried out at 2.5-4.3 V at a rate of 0.5 C, and the micromorphology of the positive electrode after regeneration was observed using SEM.
[0060] As shown in Figure 1 (a), the second charge and discharge curves of failed NCM523, regenerated electrode with lithium benzoate added, and regenerated electrode without lithium benzoate added at 0.5 C rate are shown. The discharge capacity of failed NCM523 at 0.5 C rate is only 108.5 mAh / g. The discharge capacity of the regenerated positive electrode after adding lithium benzoate can reach 148.7 mAh / g at 0.5 C rate, while the regenerated positive electrode without adding lithium benzoate only shows 136.2 mAh / g, which proves that the rapid Li after adding lithium benzoate + The transport dynamics achieved the successful repair of the failed positive electrode. As shown in Figure 1 (b), the long cycle curves of failed NCM523, regenerated electrodes with added lithium benzoate, and regenerated electrodes without added lithium benzoate at a rate of 0.5 C are shown. The results show that the regenerated positive electrode of the lithium hydroxide and lithium nitrate molten salt system with added lithium benzoate exhibits good cycle stability in the voltage range of 2.5-4.3V, and the capacity retention rates after 100, 200, and 300 cycles are 93.4%, 83.9%, and 70.1%, respectively, which are far superior to the regenerated positive electrode of the lithium hydroxide and lithium nitrate molten salt system without added lithium benzoate. As shown in Figure 1 (c), the charge and discharge capacity decay diagram of the regenerated electrode without added lithium benzoate. The regenerated positive electrode of the lithium hydroxide and lithium nitrate system without added lithium benzoate exhibits rapid capacity decay. As shown in Figure 1 (d), the charge and discharge capacity decay diagram of the regenerated electrode with added lithium benzoate. The regenerated positive electrode in the lithium hydroxide-lithium nitrate molten salt system with the addition of lithium benzoate showed slow capacity decay after 200 cycles in the voltage range of 2.5-4.3V.
[0061] As shown in Figure 2 (a), it is a schematic diagram of the scanning electron microscope of the RENCM assembled half-cell, and as shown in Figure 2 (b), it is a schematic diagram of the scanning electron microscope of the REBNCM assembled half-cell. In the SEM photos, the positive electrode particles regenerated in the lithium hydroxide and lithium nitrate molten salt system after adding lithium benzoate are intact without microcracks, while the positive electrode particles regenerated in the lithium hydroxide and lithium nitrate molten salt system without adding lithium benzoate still have some microcracks, proving that the repair is not complete.
[0062] like Figure 3 As shown in the figure, it is a schematic diagram of the principle of the direct regeneration method of the failed positive electrode of the present application. Compared with the traditional direct regeneration method of molten salt of lithium hydroxide and lithium nitrate, lithium benzoate containing benzoate is introduced into the lithium hydroxide / lithium nitrate molten salt system to repair the SNCM523 positive electrode. The addition of lithium benzoate fundamentally changes the original Li +The transport mechanism is transformed from the disordered transport driven by heat to the quasi-Grotthuss topological chemical transport mechanism promoted by the benzoate in lithium benzoate, realizing the Li + Stable coupling and decoupling in molten salts to complete Li + This transition promotes the rapid "transition" of Li + The rapid transport of the cathode ensures the full lithiation of the failed cathode surface, thus ensuring the efficient reconstruction and repair of the failed cathode structure in the subsequent high-temperature calcination stage. Therefore, the cathode material synthesized by our proposed method exhibits good electrochemical performance, which is comparable to commercial LiNi 0.5 Co 0.2 Mn 0.3 O2(CNCM) cathode, providing a promising route for efficient and sustainable regeneration of spent lithium-ion batteries.
[0063] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A direct regeneration method for a failed positive electrode, characterized in that: include: Mixing positive electrode black powder, lithium hydroxide, lithium nitrate and lithium benzoate to obtain a first mixture; Performing a pre-lithiation treatment on the first mixture assembly to obtain a pre-lithiation positive electrode powder; mixing the pre-lithiated positive electrode powder and lithium carbonate to obtain a second mixture; The second mixture is sintered to obtain a regenerated positive electrode.
2. The direct regeneration method of the failed positive electrode according to claim 1, characterized in that: The addition ratio of positive electrode black powder, lithium hydroxide, lithium nitrate and lithium benzoate is set to 1: (0.2~0.25): (0.25~0.3): 0.
5.
3. The direct regeneration method of the spent positive electrode according to claim 1, characterized in that: After obtaining the first mixture, the method further comprises: The first mixture was milled under infrared conditions.
4. The direct regeneration method of the spent positive electrode according to claim 1, characterized in that: The conditions for the pre-lithiation treatment by assembly include: keeping warm at 300° C. for 4 to 6 hours.
5. The direct regeneration method of the spent positive electrode according to claim 1, characterized in that: After the first mixture is pre-lithiated, the method further comprises: Wash with deionized water and centrifuge for multiple times, then dry to obtain pre-lithiated positive electrode powder; Grind the pre-lithiated cathode powder.
6. The direct regeneration method of a spent positive electrode according to claim 1, characterized in that: When the pre-lithiated positive electrode powder and lithium carbonate are mixed, the pre-lithiated positive electrode powder and lithium carbonate are added in a molar ratio of 1:(0.25-0.5).
7. The direct regeneration method of a spent positive electrode according to claim 1, characterized in that: The conditions for sintering the second mixture include: sintering at 750-850° C. for 6 hours.
8. The direct regeneration method of a spent positive electrode according to claim 7, characterized in that: When sintering at 750-850° C., the heating rate is 5-10° C. / min.
9. The direct regeneration method of a spent positive electrode according to claim 1, characterized in that: The positive electrode black powder is LiNi 0.5 Co 0.2 Mn 0.3 O2 black fan.
10. A regenerated positive electrode prepared by the direct regeneration method of a spent positive electrode according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for repairing and regenerating positive electrode active material of waste lithium ion battery and obtained regenerated positive electrode active material
CN112349989A
Regeneration method of integrated waste lithium ion battery layered positive electrode material
CN116169391A
Waste lithium ion battery positive electrode material regeneration method capable of synchronously realizing repair and surface coating
CN117954722A
Method for repairing and regenerating positive electrode material of lithium ion battery based on selective conversion
CN118539031A
Leaching solution and metal recovery method
US20130287654A1